Dampak Ketegangan Antaragama terhadap Perkembangan Humanitas Global di Era Digital - Mutiara Eka Putri; Tulus Suryanto; Hanif (CV. Eureka Artha Nusantara, 2026)
Religious tensions and conflicts have become a serious challenge to efforts in realizing global peace and humanitarian solidarity. This phenomenon is exacerbated by rising intolerance and radicalization through social media platforms. This paper aims to conduct a systematic literature review of journals and books published in the last five years to analyze the impact of interreligious tensions in the digital realm on global pluralism and humanism. The results of the literature review indicate that polarization among religious groups and the spread of radical narratives in cyberspace significantly weaken social solidarity and erode pluralism. To address this, existing literature emphasizes the urgency of enhancing regulations on social media use, digital literacy to build interreligious tolerance, and synergizing various institutions and stakeholders in order to promote global humanity. This research contributes by providing a contextual understanding of the relationship between interreligious tensions in the digital world and the challenges of realizing pluralism and global humanitarian solidarity. The literature review also identifies key strategies to address this issue through regulation, education, and cross-faith advocacy.